Bayes sharpening of imprecise information - Kulczycki, Piotr; Charytanowicz, Małgorzata (Zielona Góra: Uniwersytet Zielonogórski)
A complete algorithm is presented for the sharpening of imprecise information, based on the methodology of kernel estimators and the Bayes decision rule, including conditioning factors. The use of the Bayes rule with a nonsymmetrical loss function enables the inclusion of different results of an under- and overestimation of a sharp value (real number), as well as minimizing potential losses.
Keywords: imprecise information; sharpening; conditioning factors; kernel estimators; Bayes decision rule; nonsymmetrical loss function; numerical calculations